Exploring the effect of industrial agglomeration on income inequality in China - Aslam, Izah Selamat; Zhang, Suhua; Bani, Yasmin; Abdul Ghani, Judhiana (PLOS, 2023)
Income inequality is a good indicator reflecting the quality of people’s livelihood. There are many studies on the determinants of income inequality. However, few studies have been conducted on the impacts of industrial agglomeration on income inequality and their spatial correlation. The goal of this paper is to investigate the impact of China’s industrial agglomeration on income inequality from a spatial perspective. Using data on China’s 31 provinces from 2003 to 2020 and the spatial panel Durbin model, our results show that industrial agglomeration and income inequality present an inverted “U-shape” relationship, proving that they are the non-linear change. As the degree of industrial agglomeration increases, income inequality will rise, after it reaches a certain value, income inequality will drop. Therefore, Chinese government and enterprises had better pay attention to the spatial distribution of industrial agglomeration, thereby reducing China’s regional income inequality.